Discrimination of beef meat according to the level of farming intensification through visible and near infrared spectroscopy data and chemometrics - Annalaura Lopez; Elea Caumette; Rennie C. Eppenstein; Nicolò Amalfitano; Isabelle Legrand; Lynda S. Perkins; Nigel Scollan; Pablo Guarnido-Lopez; Isabelle Constant; Fabien Ferlay-Demiaz; Carmen L. Manuelian; Bruno Martin; et al. (Meat Science, 2026)

CEC01-03 The current biological understanding of the respiratory tract, the in vitro models available as well as their use - S. Constant (Toxicology Letters, 2025)

P29-08 Development of a novel in vitro platform for the detection of profibrotic compounds based on primary human alveolar epithelium - E. Pira; G. Arib; B. Boda; S. Huang; S. Constant (Toxicology Letters, 2025)

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

Monitoring macroplastics in aquatic and terrestrial ecosystems: Expert survey reveals visual and drone-based census as most effective techniques - L. Gallitelli; P. Girard; U. Andriolo; M. Liro; G. Suaria; C. Martin; A.L. Lusher; K. Hancke; MCM Blettler; O. Garcia-Garin; I.E. Napper; L. Corbari; et al. (Science of The Total Environment, 2024)

P02-47 A rat in vitro 3D airway model for translational toxicology - G. Arib; X. Huang; J. Vernaz; S. Huang; S. Constant (Toxicology Letters, 2024)

P01-62 Development of an in vitro model of dry nose - H. Xiao-Yann; J. Vernaz; S. Huang; S. Constant (Toxicology Letters, 2024)

OS01-01 Exploring extracellular and Intracellular interactions and effects of advanced materials on reconstituted primary human bronchial epithelial cultures and connecting their potential impacts on lung health - Z. Wang; J. Vernaz; M. Stange; N. Tagaras; A. Meyer-Plath; T. Buerki-Thurnherr; V.M. Kissling; S. Constant; G. Gupta; P. Wick (Toxicology Letters, 2024)

Calcifediol is a safe and effective metabolite for raising vitamin D status and improving growth and feed conversion in rainbow trout - S. Rider; V. Verlhac-Trichet; D. Constant; E. Chenal; S. Etheve; B. Riond; H. Schmidt-Posthaus; R. Schoop (Aquaculture, 2023)

Removal of Cu(II) from aqueous solution using a composite made from cocoa cortex and sodium alginate - Patrick Nkuigue Fotsing; Emmanuel Djoufac Woumfo; S. Andrada Măicăneanu; Julien Vieillard; Constant Tcheka; Patrick Tsopbou Ngueagni; Jean Mermoz Siéwé (Environmental Science and Pollution Research, 2020)

Temperature‐driven selection on metabolic traits increases the strength of an algal–grazer interaction in naturally warmed streams - C. Elisa Schaum; Richard ffrench‐Constant; Chris Lowe; Jón S. Ólafsson; Daniel Padfield; Gabriel Yvon‐Durocher (Global Change Biology, 2018)
Trophic interactions are important determinants of the structure and functioning of ecosystems. Because the metabolism and consumption rates of ectotherms increase sharply with temperature, there are major concerns that global warming will increase the strength of trophic interactions, destabilizing food webs, and altering ecosystem structure and function. We used geothermally warmed streams that span an 11°C temperature gradient to investigate the interplay between temperature‐driven selection on traits related to metabolism and resource acquisition, and the interaction strength between the keystone gastropod grazer, Radix balthica , and a common algal resource. Populations from a warm stream (~28°C) had higher maximal metabolic rates and optimal temperatures than their counterparts from a cold stream (~17°C). We found that metabolic rates of the population originating from the warmer stream were higher across all measurement temperatures. A reciprocal transplant experiment demonstrated that the interaction strengths between the grazer and its algal resource were highest for both populations when transplanted into the warm stream. In line with the thermal dependence of respiration, interaction strengths involving grazers from the warm stream were always higher than those with grazers from the cold stream. These results imply that increases in metabolism and resource consumption mediated by the direct, thermodynamic effects of higher temperatures on physiological rates are not mitigated by metabolic compensation in the long term, and suggest that warming could increase the strength of algal–grazer interactions with likely knock‐on effects for the biodiversity and productivity of aquatic ecosystems.

Metabolic compensation constrains the temperature dependence of gross primary production - Daniel Padfield; Chris Lowe; Angus Buckling; Richard Ffrench‐Constant; Simon Jennings; Felicity Shelley; Jón S. Ólafsson; Gabriel Yvon‐Durocher (Ecology Letters, 2017)
Gross primary production ( GPP ) is the largest flux in the carbon cycle, yet its response to global warming is highly uncertain. The temperature dependence of GPP is directly linked to photosynthetic physiology, but the response of GPP to warming over longer timescales could also be shaped by ecological and evolutionary processes that drive variation in community structure and functional trait distributions. Here, we show that selection on photosynthetic traits within and across taxa dampens the effects of temperature on GPP across a catchment of geothermally heated streams. Autotrophs from cold streams had higher photosynthetic rates and after accounting for differences in biomass among sites, biomass‐specific GPP was independent of temperature in spite of a 20 °C thermal gradient. Our results suggest that temperature compensation of photosynthetic rates constrains the long‐term temperature dependence of GPP , and highlights the importance of considering physiological, ecological and evolutionary mechanisms when predicting how ecosystem‐level processes respond to warming.

Toward a Regional Classification to Provide a More Inclusive Examination of the Ocean Biogeochemistry of Iron-Binding Ligands - Christel S. Hassler; Constant M. G. van den Berg; Philip W. Boyd (Frontiers in Marine Science, 2017)

The impacts, characterisation and management of human–leopard conflict in a multi-use land system in South Africa - N. L. Constant; S. Bell; R. A. Hill (Biodiversity and Conservation, 2015)

Plant Species Diversity in the Southern Part of the Taï National Park (Côte d’Ivoire) - T. Steve Denguéadhé Kolongo; Guillaume Decocq; Constant Y. Adou Yao; Edy C. Blom; Renaat S. A. R. Van Rompaey (Biodiversity and Conservation, 2006)

DDT resistance in Drosophila correlates with Cyp6g1 over-expression and confers cross-resistance to the neonicotinoid imidacloprid - P. Daborn; S. Boundy; J. Yen; B. Pittendrigh; R. ffrench-Constant (Molecular Genetics and Genomics, 2001)

Copper‐induced release of complexing ligands similar to thiols by Emiliania huxleyi inseawater cultures - M. Fernanda C. Leal; M. Teresa S. D. Vasconcelos; Constant M. G. van den Berg (Limnology and Oceanography, 1999)
Marine microalgae ( Emiliania huxleyi ) were grown in seawater enriched only with nitrogen and phosphorus, without control of free metal concentrations using synthetic chelators. Complexing ligands and thiol compounds were determined by cathodic stripping volt–ammetry. Copper was added to these cultures, and ligands were produced in response to the copper addition. Parallel measurements of thiols showed that glutathione and other unidentified thiols (electrochemically similar to thioacetamide) were produced by the algae at rates and concentrations similar to those of the complexing ligands. Smaller amounts of thiols were produced when ligands including thiols were added to the culture. The results indicate that thiols can account for a major part or most of the copper–complexing ligands produced by these algae. Furthermore, a feedback mechanism exists in which the production of thiol–type complexing ligands is controlled by the free copper concentration, production already being stimulated by an increase of [Cu 2+ ] from 0.4 to 1.5 pM. Incubations with added exudates, thiols, and salicylaldoxime (SA) showed much reduced copper toxicity even though copper uptake was increased by the exudates and the SA.

Analysis of some morphological and biochemical characteristics of the egg of the predaceous bugMacrolophus caliginosus (Het.: Miridae) during embryogenesis - B. Constant; S. Grenier; G. Bonnot (BioControl, 1994)